Applying Business Process Re-Engineering to Public Sector as A New Public Management Strategy - Ropinder Oberoi (Jurnal Studi Pemerintahan, 2013)
The introduction of Business process Reengineering (BPR) to the public sector follows the much broader trend of New Public Management. BPR in the public sector mostly means amalgamation of business processes, computerization of various activities and removal of some unnecessary ones. BPR assimilates a radical premeditated scheme of business process reengineering and an additional progressive technique of uninterrupted process improvement with adequate information technology (IT) and e-business infrastructure strategies. Public organisations have specific and exclusive features that differentiate them from private sector organisations. Based on the literature review and examining of study findings, it is argued that a public sector organisation can employ BPR to get better its process and overall organisational performance, if it (1) has accrues a collection of BPR-relevant resources and capabilities; (2) has embarked on BPR with adequate depth and breadth; (3) is developing a post-BPR complementary set of skills, systems and technologies, which are essential to further develop the organisational impact of the BPR; and (4) has successfully mitigated the effects of BPR implementation problems. In addition to its effect on administration and service delivery processes through reduction of the processing time, work steps and cost of government processes, BPR also contributes to enhancing citizen/customer and employee satisfaction, increasing organisational transparency and responsiveness which have also become an essential objective of New Public Management. Therefore, public sector BPR is emerging as an indispensable to performance o f organisations in the developing economy. The essential questions addressed in this paper are: What are the scenario and impending problems of reengineering applications in the public sector? Can it be functional for the public sector in attending to frequent problems blockading bureaucracies of developed and developing countries uniformly? What are the implementational vulnerabilities faced by public sector while deploying BPR.